Problematic aspects of material liability of transport workers - Синенко, Світлана Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article investigates the problematic aspects of the material liability of transport workers. Based on the analysis of the current legislation a theoretical study of the legal regulation of material liability for transport workers has been conducted, and the need to improve the regulations that govern this issue has been emphasized. It is concluded that the transport workers bear limited and full liability for damage caused to the employer with whom they are employed. Thus, the transport workers whose work is directly related to running vehicles have limited material liability in the amount of actual direct damages, but no more than their average earnings, as specified in the Labor Code of Ukraine. If the damage exceeds the average salary of the employee, the damage remains uncompensated portion of the guilty employee. The employer is required to reimburse the portion of losses not compensated by the employee (to repair the vehicle, to compensate the damage in full to third parties caused by fault of the employee while performing job duties). The article proves that the current labor legislation of Ukraine, which regulates the financial responsibility of the transport workers, whose work is directly related to running vehicles, needs to be revised to protect the property rights of the employer from causing harm caused by this category of workers due to violations of their labor required 'bonds. Therefore, the author thinks that clause 1, Art. 338 of the draft Labor Code of Ukraine should be complemented with part 6 and read as follows: "6) controlled vehicles of all transport modes."